Genetic polymorphism of CYP genes, alone or in combination, as a risk modifier of tobacco-related cancers - Bartsch, Helmut; Risch, Angela (Cancer epidemiology, biomarkers & prevention, 2000)
Tobacco use is causally associated with cancers of the lung, larynx, mouth, esophagus, kidneys, urinary tract, and possibly, breast. Major classes of carcinogens present in tobacco and tobacco smoke are converted into DNA-reactive metabolites by cytochrome P450 (CYP)-related enzymes, several of which display genetic polymorphism. Individual susceptibility to cancer is likely to be modified by the genotype for enzymes involved in the activation or detoxification of carcinogens in tobacco and repair of DNA damage. We summarize here the results of case-control studies published since 1990 on the effects of genetic variants of CYP1A1, 1A2, 1B1, 2A6, 2D6, 2E1, 2C9, 2C19, 17, and 19 alone or in combination with detoxifying enzymes as modifiers of the risk for tobacco-related cancers. The results of studies on gene-gene interactions and the dependence of smoking-related DNA adducts on genotype were also analyzed. Some CYP variants were associated with increased risks for cancers of the lung, esophagus, and head and neck. The risk was often increased in individuals who also had GSTM1 deficiency. For breast cancer in women, a few studies suggested an association with CYPs related to metabolism of tobacco carcinogens and steroidal hormones. The overall effects of common CYP polymorphisms were found to be moderate in terms of penetrance and relative risk, with odds ratios ranging from 2 to 10. Some CYP1A1/GSTM1 0/0 genotype combinations seem to predispose the lung, esophagus, and oral cavity of smokers to an even higher risk for cancer or DNA damage, requiring, however, confirmation. Future strategies in molecular cancer epidemiology for identifying such susceptible individuals are discussed with emphasis on well-designed larger studies.
Gesehen am 02.02.2021